Aktivitas Antioksidan dan Antibakteri Ekstrak Etanol Buah Ihau (Dimocarpus longan var. malesianus Leenh) Terhadap Bakteri Gram Positif (Staphylococcus aureus) - Irma Sarita Rahmawati; Rahma Micho Widyanto; Annisa Rizky Maulidiana; Muhammad Surya Madani; Choirun Nisa Riski (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Ihau fruit (Dimocarpus longan var. malesianus Leenh) is a typical Kalimantan fruit which has a longan-like morphology. The vitamin C content and various phytochemical compounds of ihau has the potential as a natural antioxidant and antibacterial agent. This study aimed to determine the potential antioxidant and antibacterial activity of ihau extract on Staphylococcus aureus bacteria in vitro with a post-test only control group design. Samples were extracted with 96% ethanol and water using the maceration method. Antioxidant activity measured using DPPH test. Antibacterial test using well diffusion method was performed in six treatment groups (ethanol extract concentration 50, 60, 70, 80, 90, 100mg/ml), positive control (Ampicillin) and negative control (sterile distilled water). The results showed that IC50 value for the ethanol extract of ihau was 681.05 g/ml and the aqueous extract was 698.3 g/ml. The antibacterial test indicated that ethanol extract had an inhibitory effect on the growth of Staphylococcus aureus at 70 mg/ml to 100 mg/ml concentration. It can be concluded that ihau fruit extract has antibacterial ability against gram positive bacteria (Staphylococcus aureus) but does not have antioxidant activity.Keywords - Ihau fruit, ethanol extract, antioxidant, antibacterial, Staphylococcus aureus.